Navigating AI in higher education: examining overreliance and plagiarism among UiTM Tapah students - Sarkam, Nor Aslily; Mohammad, Nor Hazlina; Saiful Lizam, Nurizatie Farhanim; Azmi, Nurul Ain; Mazli, Nadhira Yasmin; Mohd Dzahir, Mizan Qamalia; Md Isa, Ros Amira Arisha (UiTM Cawangan Perlis, 2025)
The rapid advancement of Artificial Intelligence (AI) has transformed various sectors, including higher education. This study explores the challenges and opportunities of AI tool adoption in higher education, focusing on student learning experiences and ethical considerations. By employing correlation and regression analysis, this research analyzes data from 357 students to examine key factors influencing AI adoption, including effort expectancy, performance expectancy, digital literacy, and behavioural intention. The findings suggest that digital literacy significantly affects students' acceptance of AI tools, reinforcing the importance of targeted educational interventions. While AI integration enhances learning efficiency and accessibility, ethical concerns such as data privacy, algorithmic bias, and academic integrity remain critical challenges. The study provides insights for educators, policymakers, and institutions to develop strategies that balance technological advancements with ethical responsibility, ensuring an inclusive and effective AI-driven educational environment. Future research should explore longitudinal impacts and cross-cultural variations in AI adoption.